Arah Reforma Agraria di Indonesia - Monsaputra, Monsaputra (Department of Political Science - Universitas Sains Al-Qur’an, 2025)
Agrarian reform aims to equalize the structure of control, ownership, use and utilization of land, resolve agrarian conflicts and realize a just economy. Presidential Regulation Number 62 of 2023 concerning the acceleration of the implementation of agrarian reform as an effort to accelerate the fulfillment of the target of providing land for agrarian reform objects and the implementation of land redistribution, legalization of transmigration land assets, resolution of agrarian conflicts, and economic empowerment of agrarian reform subjects. This study aims to analyze the direction of the development of agrarian reform. The method of analysis used was normative juridical using a descriptive analysis approach. The results of the study are that agrarian reform is not limited to land redistribution activities but also includes asset legalization. Existing legal products have provided space for the implementation of optimal agrarian reform. The main source of land that is the object of agrarian reform should be maximum excess land, because this will create justice in land control and ownership.